PENGARUH PENGGUNAAN MODEL PEMBELAJARAN ABAD 21 TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK SEKOLAH DASAR - Ida Rahmawati (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
Abstract: This study aims to determine whether there is a significant effect on the use of 21st century learning models on the cognitive abilities of elementary school students. This study uses a quantitative approach with quantitative survey methods and submits questionnaires according to research variables with valid instruments totaling 16 items, there are 85 respondents who return answers which are then processed in simple regression statistical analysis assisted by SPSS 24. The results of the study have a significant effect on the use of learning models. 21st century on cognitive learning outcomes and accepted hypotheses, including the subjects of Islamic Religious Education (PAI). By using the right learning model, it is easier for students to master the material and learning outcomes are better and increase. The learning models applied are PBL, PjBL and inquiry (collaboration and group based). And learning conditions will be comfortable and fun, namely learner-centered learning. Keywords: 21st Century Learning Model, Islamic Religious Education, Cognitive Ability, Elementary School Students. Abstrak: Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh signifikan pada penggunaan model pembelajaran abad 21 terhadap kemampuan konitif peserta didik sekolah dasar. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey kuantitatif dan menyampaikan kuesioner sesuai variabel penelitian dengan intrumen yang valid berjumlah 16 item, terdapat 85 responden yang mengembalikan jawaban yang kemudian di olah dalam analisis statistik regresi sederhana berbantuan SPSS 24. Hasil penelitian terdapat pengaruh signifikan penggunaan model pembelajaran abad 21 terhadap hasil belajar kognitif dan hipotesis diterima, termasuk pada mata pelajaran Pendidikan Agama Islam (PAI). Dengan penggunaan model pembelajaran yang tepat peserta didik lebih mudah menguasai materi dan hasil belajar lebih baik dan meningkat. Model pembelajaran yang diterapkan adalah PBL, PjBL dan inquiry (berbasis kolaborasi dan kelompok). Serta kondisi pembelajaran akan berjalan nyaman dan menyenangkan, yakni pembelajaran berpusat pada peserta didik. Kata Kunci: Model Pembelajaran Abad 21, Pendidikan Agama Islam, Kemampuan Kognitif, Peserta didik Sekolah dasar.